Design, synthesis and evaluation of polymers for affinity based enzyme separations - Vaidya, A. A. (CSIR-National Chemical Laboratory, 2000)
A wide range of techniques have been developed for the separation and recovery of different biomolecules. Amongst these, the affinity based techniques viz. affinity chromatography, affinity ultrafiltration and affinity two-phase aqueous extraction are attractive as they provide high specificity and selectivity during separation as compared to the conventional methods. Although selective, these techniques are beset with major shortcomings. To name a few, fouling of the membranes in affinity ultrafiltration, low capacity and flow rate limitations in affinity chromatography and contamination of the polymeric phase with final product in two-phase extraction. The affinity precipitation technique overcomes many of the problems associated with membrane filtration and affinity chromatography. It offers ease of scale up, concentration and purification, which could be achieved in a single step. It is amenable to continuous operation and the affinity ligand can be recycled. A large number of enzymes separated using this technique. With continued investigations, many shortcomings of affinity precipitation too were realized. It suffers from limited stability of many natural affinity ligands, decrease in the affinity of ligand when incorporated in the polymer due to crowding effect, and steric hindrance posed by the high molecular weight polymers. The present investigation was undertaken to design and synthesize new affinity polymers that would overcome the crowding effect and enhance the ligand-enzyme binding in affinity thermoprecipitation process. To adapt and demonstrate this methodology for the recovery of a commercially valuable enzyme, lysozyme was selected as a candidate. A comparative analysis of recovery of lysozyme by acidic thermoprecipitating polymers versus affinity based synthetic/natural ligands has been done. In the recent past, molecular imprinting technique has been employed in various bioseparations. In this, secondary valance interactions such as hydrogen bonding, ionic and hydrophobic interactions are exploited not only during synthesis of an imprinted polymer but also during rebinding studies. Since only weak interactions are involved in the rebinding of the desired molecule, the selectivity and capacity of such imprinted receptors is often low. In order to improve on this the enzyme-affmity ligand interactions are exploited during synthesis of molecularly imprinted polymers.